Moderasi Beragama dalam Praktik Safari Ramadhan: Refleksi Pengabdian Mahasiswa - Noptario, Noptario; Hulkin, M.; Irawan, M. Ferry; Solihin, Ilham; Zakaria, Abd Razak (Ngarsa: Journal of Dedication Based on Local Wisdom, 2024)
Indonesia has diverse ethnic groups, religions, and cultures. This diversity can trigger identity conflicts if not appropriately managed; therefore, a non-extreme understanding is required. One of the obligations of university students is to carry out community service, including efforts to strengthen religious moderation. This community service's purpose is to explore efforts to strengthen religious moderation through the Safari Ramadan activities conducted by the Special Student Activity Unit for the Institute for Quranic Recitation Development and Da'wah (UKMK LPTQ & D) at UIN Raden Fatah Palembang and its implications for the community, the campus, and members of UKMK LPTQ & D. This research adopts a descriptive qualitative approach. Data were collected through interviews and observations, and semi-structured interviews were conducted with students and community members. Based on the findings, the efforts to strengthen religious moderation during the Ramadan Safari activities reached all age groups, including children, adolescents, youth, and adults. These efforts were implemented through various programs, such as religious moderation seminars, religious moderation studies in mosques, religious moderation quiz competitions, and training on religious moderation for adolescents and youth. Keywords: Religious moderation, Safari Ramadhan, University student Abstrak: Indonesia memiliki beragam suku, agama, dan budaya. Keberagaman ini dapat memicu konflik identitas apabila tidak dikelola dengan baik. Untuk menghadapinya, diperlukan pemahaman yang tidak ekstrem. Salah satu kewajiban mahasiswa di perguruan tinggi adalah melaksanakan pengabdian kepada masyarakat, antara lain dalam hal penguatan moderasi beragama. Tujuan pengabdian ini adalah mengungkap upaya penguatan moderasi beragama dalam kegiatan Safari Ramadhan yang dilaksanakan oleh Unit Kegiatan Mahasiswa Khusus Lembaga Pengembangan Tilawatil Qur'an dan Dakwah (UKMK LPTQ & D) UIN Raden Fatah Palembang, serta implikasinya terhadap masyarakat, kampus, dan anggota UKMK LPTQ & D. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Data dikumpulkan melalui wawancara dan observasi. Wawancara dilakukan secara semiterstruktur terhadap mahasiswa dan masyarakat. Berdasarkan temuan penelitian, penguatan moderasi beragama dalam kegiatan Safari Ramadhan menjangkau semua kelompok usia, mulai dari anak-anak, remaja, pemuda, hingga orang tua. Upaya penguatan moderasi beragama dilakukan melalui berbagai program, seperti seminar moderasi beragama, kajian moderasi beragama di masjid, lomba cerdas cermat moderasi beragama, dan pelatihan moderasi beragama bagi remaja serta pemuda. Kata kunci: Moderasi beragama, Safari Ramadhan, Student community service